Optimization Day Old Chick Incubator Design to Reduce Mortality Rate Using Fuzzy Logic - Saputro, Adi Kurniawan; Ramadhan, Muhammad Fajar; Ibaidilah, Achmad Fiqhi; Haryanto, Haryanto; Sukri, Hanifudin; Hardiwansyah, Muttaqin (Signal and Image Processing Letters, 2025)
In poultry farming, particularly for Day-Old Chicks (DOC), maintaining an ideal environmental condition is a significant challenge due to the limited ability of mother hens to provide adequate warmth and care. This often leads to a high mortality rate among DOC, especially in broiler chickens. The research contribution is the development of an intelligent incubator system based on fuzzy logic to automate environmental control and reduce DOC mortality rates. The system employs a DHT22 sensor to measure temperature and humidity, and an MQ-135 sensor to detect ammonia levels. An ESP32 microcontroller is used for data processing, chosen for its built-in Wi-Fi capability and high processing power. The DHT22 sensor controls a fan and UVA+UVB lamp via an AC dimmer, while the MQ-135 sensor controls a DC motor through the L298N driver. The fuzzy logic method is applied to make more accurate control decisions, and the entire system is connected to an IoT-based monitoring platform that provides a real-time dashboard for farmers. Preliminary results show that the system successfully maintains temperature within the optimal range (30–34?) and humidity (40–70%), and responds efficiently to changes in ammonia concentration. Compared to conventional systems, this intelligent incubator offers better automation, lower energy consumption, and cost efficiency. In conclusion, the proposed system provides a scalable and efficient solution for DOC management. Future work includes AI-based prediction integration, mobile application development, and historical data analysis for smarter poultry farm management.